A NEW SPECIES OF TINOSPORA (MENISPERMACEAE) FROM SOUTH INDIA - Udayan, P. S.; Pradeep, A. K.; Balachandran, Indira (Edinburgh Journal of Botany, 2009)
A new species of Tinospora (Menispermaceae), Tinospora formanii Udayan & Pradeep from the Western Ghats of Thrissur district, Kerala, South India, is described and illustrated.